Liberating the mental health and wellbeing benefits of laughing alone: a new taxonomic model and scoping review for future research - Freda Gonot-Schoupinsky; Xavier Gonot-Schoupinsky; Mark Weeks (Discover Mental Health)
Abstract Laughter has been predominantly viewed as a social behavior, and laughing alone is often regarded doubtfully, even pathologized. While solitary laughter can be symptomatic of mental health issues, one motivation of this review was to explore whether it can also offer mental health benefits. Research demonstrates that over 10% of laughter occurs in solitude and there is increasing awareness that it is not only enjoyed but can serve important roles in supporting health and wellbeing. To establish a useful foundation for further exploration of its potential in enhancing health and wellbeing, this review scopes the subject across disciplines. An unprecedented search revealed 120 records (n = 83 academic articles n = 37 literary and book references) that mention solitary laughter in meaningful ways. The Solitary Laughter Model (SLM) developed for this research supported an initial classification according to the conditions in which the laughter took place be it complete solitary, public solitary, assisted solitary, or social solitary laughter. Our research reveals that laughing alone tends to be perceived as particularly problematic when done in public. Nevertheless, we also uncovered favorable mental health perspectives on solitary laughter and recent exciting clinical applications in assisted solitary laughter. The implications of these findings are discussed. The SLM is proposed as a pragmatic model to encourage precision in this nascent field of investigation and health practice. This review concludes that solitary laughter is an important human behavior deserving more scientific investigation to further unlock its mental health and wellbeing benefits.